The Role of Proportion in the First-Movement Expositions of Mozart's String Quintets - Sola Chagas Lima, Eduardo (Revista Vórtex, 2014)
This study aims at discussing the role of balance and proportion in the expositional scope within a Classical Sonata Form movement. While using the approach, model and labels proposed by James Hepokoski and Warren Darcy in Elements of Sonata Theory (2006), it also challenges the application of some of their analytical tools. Throughout this study, special attention is given to different treatments of expositional spaces, including a few significantly difficult cases for the repertoire. The intention here is to observe the interaction between these spaces in light of the dual function in the expositional trajectory: (1) to fulfill the harmonic requirement in destabilizing the tonic key; and (2) to attain a rhetorically reasonable organization of thematic material (HEPOKOSKI; DARCY, 2006, p.18). For this purpose, a careful examination of the medial caesura and the essential expositional closure is also taken into account throughout the present analysis. Finally, however limited the repertoire range used in this specific research, the present study fosters the idea of proportion and balance as feasible arguments (among many others) not only in determining the dimensions of expositional spaces, but also in the holistic process of analyzing entire Classical sonata forms as hermetic units.